Ultraclean individual suspended single-walled carbon nanotube field effect transistor. (2nd March 2018) - Liu, Siyu; Zhang, Jian; Nshimiyimana, Jean Pierre; Chi, Xiannian; Hu, Xiao; Wu, Pei; Liu, Jia; Wang, Gongtang; Sun, Lianfeng
Abstract: In this work, we report an effective technique of fabricating ultraclean individual suspended single-walled carbon nanotube (SWNT) transistors. The surface tension of molten silver is utilized to suspend an individual SWNT between a pair of Pd electrodes during annealing treatment. This approach avoids the usage and the residues of organic resist attached to SWNTs, resulting ultraclean SWNT devices. And the resistance per micrometer of suspended SWNTs is found to be smaller than that of non-suspended SWNTs, indicating the effect of the substrate on the electrical properties of SWNTs. The ON-state resistance (∼50 kΩ), mobility of 8600 cm 2 V –1 s –1 and large on/off ratio (∼10 5 ) of semiconducting suspended SWNT devices indicate its advantages and potential applications.